Hypomorphism for RPGRIP1L, a ciliary gene vicinal to the FTO locus, causes increased adiposity in mice - Stratigopoulos, George (2014)
Common polymorphisms in the first intron of FTO are associated with a increased body weight in adults. Previous studies have suggested that a CUX1 regulatory element within the implicated FTO region controls expression of FTO and the nearby ciliary gene, RPGRIP1L. Given the role of ciliary genes in energy homeostasis, we hypothesized that mice hypomorphic for Rpgrip1l would display increased adiposity. We find that Rpgrip1l(+/−) mice are hyperphagic, fatter, and display diminished suppression of food intake in response to leptin administration. In the hypothalamus of Rpgrip1l(+/−) mice, and in human fibroblasts with hypomorphic mutations in RPGRIP1L, the number of AcIII-positive ciliais diminished, accompanied by impaired convening of the leptin receptor to the vicinity of the cilium, and diminished pStat3 in response to leptin. These findings suggest that RPGRIP1L may be partly or exclusively responsible for the obesity susceptibility signal at the FTO locus.